Investigative Journalism in Lithuania 2015–2020 - Račiukaitytė, Rūta (Žurnalistikos tyrimai, 2021)
The article analyzes investigative journalism in Lithuania in 2015–2020 to determine the particularity of changes in investigative journalism. Until then, only one research on investigative journalism was conducted in Lithuania, indicating that in 2015 there was no investigative journalism as a type of media in Lithuania. Although, investigative journalism is a public control tool aimed at exposing corruption and possible criminal activity.And in 2015, the first research department was established in Lithuania as part of the structure of the media. The work aims to find out how investigative journalism has changed in Lithuania during the last years 2015-2020 and to single out the essential factors that would allow to evaluate the development of investigative journalism. The article presents the author‘s model of investigative journalism and the peculiarities of the change of investigative journalism in Lithuania. It has been established that the situation of investigative journalism in Lithuania is improving, however, compared to the media systems of Western countries, it remains underdeveloped. The perception of experts on investigative journalism is revealed, the reasons for the formation of structural structures of investigative journalism, Lithuania‘s role in international investigative journalism organizations, representatives of investigative journalism are singled out and their research is carried out, research topics, areas, applied research methods
Keywords: Investigative journalism in Lithuania; peculiarities of change; international organizations of investigative journalism; representatives of investigative journalism; financing